(untitled) (Journal of the College of Basic Education, 2025)
This research aims to investigate wisdom-based thinking and its relationship to job satisfaction among secondary school teachers. The current study is limited to secondary school teachers within the Directorate of Education of Baghdad Al-Rusafa First for the academic year (2024–2025). The research population consists of all teachers working in secondary schools under this directorate, totaling (1,452) teachers. A stratified random sample of (200) teachers was selected, representing 5% of the total population. For the first variable (wisdom-based thinking), the researcher adopted a pre-developed scale by Mohammed (2024), which consists of (40) items. For the second variable (job satisfaction), the researcher used a pre-developed scale by Al-Shannaq (2001), which consists of (47) items. Both instruments were adapted and their face validity was verified by presenting them to a panel of experts, in addition to verifying their construct validity. The validity and reliability of both instruments were calculated. The data were analyzed using the Statistical Package for the Social Sciences (SPSS), employing several statistical methods including Chi-square test, independent samples t-test, one-sample t-test, Pearson correlation coefficient, and Cronbach’s alpha coefficient. The study concluded that wisdom-based thinking is prevalent among secondary school teachers and that there is a positive correlation between wisdom-based thinking and job satisfaction.